1978
DOI: 10.1136/hrt.40.6.650
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of intravenous metoprolol in man.

Abstract: sUMMARY Electrophysiological changes produced by intravenous (0 1 mg/kg) metoprolol, a new selective Pli-blocking agent devoid of intrinsic activity, were studied in 16 subjects with estimated normal impulse formation and conduction.The most important effects were sinus bradycardia, mild increase of sinoatrial conduction time, depression ofintranodal conduction, and prolongation of AV node refractory periods. Sinus node recovery time and atrial refractoryperiodswere unmodified. Infranodal conduction and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…The depressant effect of P-adrenoceptor blockade at the level of the sinus node, as indicated by heart rate, sino-atrial conduction time, sinus node recovery time and corrected sinus node recovery time, seems to be most pronounced with atenolol (di Biase etal., 1977;Robinson etal., 1978;Seipel etal., 1977). However, a prolongation of the sinus node recovery times was not observed with pindolol (di Biase et al, 1977a), oxprenolol (di Biase et al, 1977b, metoprolol (Rizzon et al, 1978), tolamolol (Alboni et al, 1977), acebutolol (Mason et al, 1978) or penbutolol (von Leitner & Biamino, 1980). A prolongation of the sino-atrial conduction times was also found with metoprolol (Rizzon et al, 1978) and acebutolol, whereas this parameter was not changed by propranolol (Seipel et al, 1977), oxprenolol (di Biase et al, 1977b and pindolol (di Biase et al, 1977a).…”
Section: Discussionmentioning
confidence: 99%
“…The depressant effect of P-adrenoceptor blockade at the level of the sinus node, as indicated by heart rate, sino-atrial conduction time, sinus node recovery time and corrected sinus node recovery time, seems to be most pronounced with atenolol (di Biase etal., 1977;Robinson etal., 1978;Seipel etal., 1977). However, a prolongation of the sinus node recovery times was not observed with pindolol (di Biase et al, 1977a), oxprenolol (di Biase et al, 1977b, metoprolol (Rizzon et al, 1978), tolamolol (Alboni et al, 1977), acebutolol (Mason et al, 1978) or penbutolol (von Leitner & Biamino, 1980). A prolongation of the sino-atrial conduction times was also found with metoprolol (Rizzon et al, 1978) and acebutolol, whereas this parameter was not changed by propranolol (Seipel et al, 1977), oxprenolol (di Biase et al, 1977b and pindolol (di Biase et al, 1977a).…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol, the most studied and most widely employed drug, increases the basic sinus cycle length, and the atrioventricular intranodal conduction time, lowers the artificial atrial rate of the Wenckebach point, and has no effect on the His-Purkinje system. The majority of beta blockers used in humans have similar effects (DiBiase er al., 1977a,b, 1978Mason et al, 1978;Nathan et al, 1982;Rizzon et al, 1978;Ruskin et al, 1975), which explains the antiarrhythmic effects of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many of them were studied (DiBiase et ul., 1977a(DiBiase et ul., ,b, 1978Mason et al, 1978;Nathan et ul., 1982;Rizzon et al, 1978;Ruskin et ul., 1975) and it was confirmed that they have actions that are comparable to propranolol (Seides et al, 1974), which is in wide use in several countries. However, some of them have side effects that limit their use.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that different betablockers delay impulse propagation via the normal atrioventricular conduction pathway (3,4,12). Electrophysiological studies reveal an increased sino-atrial conduction time, depressed intranodal conduction and prolongation of the refractory period of the A V node after metoprolol (11).…”
Section: A Khalsa Et Al: Metoprolol and Digitalis In Atrial Fibrillamentioning
confidence: 99%
“…50 mg of metoprolol was administered immediately after the control measurement and another 50 mg after the 30 min recording. ECGs were recorded at 1/2 hourly interval at a work load of 40 W for 4 min during a period of 3 h. Metoprolol slows atrioventricular conduction not only during sinus rhythm (11), but also during atrial fibrillation (13). Several studies have indicated that different betablockers delay impulse propagation via the normal atrioventricular conduction pathway (3,4,12).…”
Section: A Khalsa Et Al: Metoprolol and Digitalis In Atrial Fibrillamentioning
confidence: 99%